Sequencing and de novo assembly of a Dahlia hybrid cultivar transcriptome - Lehnert, Erik M.; Walbot, Virginia (Frontiers in Plant Science, 2014)
Dahlia variabilis, with an exceptionally high diversity of floral forms and colors, is a popular flower amongst both commercial growers and hobbyists. Recently, some genetic controls of pigment patterns have been elucidated. These studies have been limited, however, by the lack of comprehensive transcriptomic resources for this species. Here we report the sequencing, assembly, and annotation of the transcriptome of the developing leaves, stems, and floral buds of D. variabilis. This resulted in 35,638 contigs, most of which seem to contain the complete coding sequence, and of which 20,881 could be successfully annotated by similarity to UniProt. Furthermore, we conducted a preliminary investigation to identify contigs with expression patterns consistent with tissue-specificity. These results will accelerate research into the genetic controls of pigmentation and floral form of D. variabilis.